Kajian Internalisasi Nilai Kekidungan Jawa Dalam Kalangan Pemuda Hindu Di Kabupaten Pringsewu-Lampung - Sugiyarto Sugiyarto; I Made Biasa; Ni Nyoman Sudiani (Pasupati, 2022)
This study discusses of the internalization the value of Kekidungan Javanese in Hindu youth Pringsewu Regency-Lampung. This research is a qualitative research using descriptive method. This study tries to reveal how the understanding and internalization of Kekidungan Javanese grew through the internalization process in the Hindu community, especially the Hindu Youth in Pringsewu-Lampung. This study resulted in the following findings: (A) The Hindu Community’s Understanding of Kekidungan Javanese of Song in Pringsewu Contains: 1) Understnading of Kekidungan as kinaryo dungo (mantra); 2) The types of chants that have developed include (a) Kekidungan macapat such as kinanthi, asmarandana, asmarandana, dhandanggula, pangkur, megatruh, pucung; and (b) Kekidungan panembromo such as the ayak-ayak pamungkas, and ibu pertiwi; 3) Understanding is shaped by experience. (B) The internalization of Javanese chant in the Hindu Community in Pringsewu-Lampung contains: 1) the song is internalized at religious events such as kliwonan, purnama, tilem and social events at people’s homes (anjangsana); 2) The learning process is carried out in the Paguyuban and self-study; 3) kekidungan is able to mobilize Hindu Youth to learn Javanese culture which occurs through the internalization process; 4) internalization of Kekidungan Javanese values in the Hindu community in Pringsewu-Lampung includes (a) aesthetic values, (b) social values, (c) religious values. This research is expected to be developed, so that it can be a guide for human life to achieve safety and peace.